Potential for external reinforcement of insulated rail joints. (March 2018) - Gallou, M; Temple, B; Hardwick, C; Frost, M; El-Hamalawi, A
This paper aims to investigate the alternative ways of reducing the deterioration and failure of insulated rail joints of railway tracks. Joints deteriorate faster than rails due to the presence of structural discontinuity. This weakness results in extra displacement due to the applied load and dynamic force that results as a consequence. Overtime, this situation worsens as the impacts and applied stresses damage and soften the ballast and the supporting subgrade under the joint. This study initially presents a static finite element model designed to simulate the mechanics of insulated rail joints, and then a comparison is made between the plain rail and a suspended insulated rail joint under various support stiffnesses. The product design options of the reinforced insulated rail joints are then chosen as input variables of the model. The results of the model are compared with the field and laboratory data acquired via the Video Gauge, which is a new high-resolution optical measurement technique. The results show that the use of strap rails or more robust I-beam sections in the vicinity of the insulated rail joint to stiffen the support structure can significantly reduce the displacement and the subsequent dip angle seen in an insulated rail joint. This potentially presents a means of improving the behaviour of the insulated rail joints. Their impact becomes more significant for soft support conditions. Although these results are indicative of new conditions for insulated rail joints, the field measurements indicate that the magnitude of deflection of insulated rail joints is a result of the structural discontinuity of the rails, the dynamic P2 force, the wheel condition, the degraded ballast and it significantly increases with time under repeated load. Thus, it is recommended that a careful field implementation and testing will indicate the effect of an external enhancement on the timely degradation of insulated rail joints.